The Utilization and Impact of Aromatase Inhibitor Therapy in Men With Elevated Estradiol Levels on Testosterone Therapy. Issue 4 (3rd June 2021) - Punjani, Nahid; Bernie, Helen; Salter, Carolyn; Flores, Jose; Benfante, Nicole; Mulhall, John P.
Abstract: Introduction: Testosterone therapy (TTH) for testosterone deficiency (TD) may lead to elevated estradiol (E2) levels requiring management to avoid unnecessary adverse effects. Aim: To examine the impact of aromatase inhibitors, specifically anastrozole (AZ), in men with elevated E2 on TTH. Methods: All patients on TTH at a high volume sexual medicine practice between 2005 and 2019 were reviewed. Men with E2 levels >60 pg/mL regardless of symptoms or 40–60 pg/mL with subjective symptoms were started on AZ 0.5 mg 3x/week. Routine hormone profile and symptom assessment were completed to ensure symptom resolution, reduction of E2 levels and maintenance of testosterone levels. Multivariable logistic regression was completed to determine predictors of men more likely to respond to therapy. Main Outcome Measure: Demographic and hormonal profiles of men on AZ and predictors of response to therapy. Results: 1708 men with TD were placed on TTH. Of these, 51 (3%) were treated with AZ (AZ+). After exclusions, 44 (2.6%) had elevated estradiol levels >60 pg/mL or >40 pg/mL with symptoms. Demographics were similar between groups. TTH distribution between groups was different with greater rates of topical TTH in the AZ- groups (AZ+:34.1% vs AZ-:53.5%) and greater rates of intramuscular TTH in the AZ+ group (AZ+:38.6% vs AZ-:18.5%) ( P = . 017 overall). Of the 44 men treated with AZ, 68.0% had pre-AZ E2 levels ≥60 pg/mL and 32.0% had levels between 40 and 60 pg/mL. Median pre-AZ E2 levels were 65 (interquartile range [IQR], 55–94) pg/mL in comparison to 22 (IQR 15–38) pg/mL post-AZ E2 levels ( P < . 001). Total testosterone levels were similar before and after AZ use (616 (IQR 548–846) ng/dL and 596 (IQR 419–798) ng/dL, respectively, P = . 926). No statistically significant predictive factors of E2 reduction using AZ were found. Conclusion: While no statistically significant predictors for E2 recovery in men on AZ were found, AZ remains a reasonable option for E2 reduction in men with elevated levels on TTH. Punjani N, Bernie H, Salter C, et al. The Utilization and Impact of Aromatase Inhibitor Therapy in Men With Elevated Estradiol Levels on Testosterone Therapy. Sex Med 2021;9:100378 .